2D multichannel seismic reflection raw data (GI Gun) of RV SONNE cruise SO182 in 2005 to the Agulhas Bank, seismic reflection profile AWI-20050101 - Uenzelmann-Neben, Gabriele (PANGAEA, 2025)
Seismic reflection data collected in the Agulhas Bank during cruise SO182 with RV Sonne in 2005. 8 G-guns and a 32 l Bolt airgun were used a seismic source, the data were recorded with a 2250 m (active length) long digital streamer. The data are unprocessed. No gain, filter or mute have been applied. The data are in SEGY format. See cruise report (Uenzelmann-Neben, 2005) or ReadMe file for more information on acquisition parameters.
Keywords: Agulhas Bank; AWI Geophysics; Seismic reflection